Enhanced H-bonding and pi-stacking in DNA: a potent duplex-stabilizing and mismatch sensing nucleobase analogue - Lou, C; Dallmann, A; Marafini, P; Gao, R; Brown, T (Royal Society of Chemistry, 2014)
X-pyrene is a new nucleic acid duplex stabilizing cytosine analogue that combines enhanced π-stacking, hydrogen bonding and electrostatic interactions to greatly increase the stability of bulged DNA duplexes and DNA/RNA hybrids. X-pyrene is highly selective for guanine as a partner and duplex stability is reduced dramatically when X-pyrene or a neighboring base is mismatched. An NMR study indicates that the pyrene moiety stacks within the helix, and large changes in fluorescence emission on duplex formation are consistent with this. These favorable properties make X-pyrene a promising cytosine analogue for use in a variety of biological applications.